2002
DOI: 10.1007/s00417-002-0444-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of penetrating keratoplasty using a single or double running suture technique

Abstract: Although the final astigmatism was about the same in the two suture groups, the DRS seems to lead to faster restoration of visual function due to early stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…31,32 Final astigmatism is almost the same with single running suture and double running suture techniques. 33 Other authors have shown that an adjustable single running suture is better than a double running suture in managing postsurgical astigmatism. 34 Busin et al 30 report that double running sutures with 16 bites each are superior to 16 interrupted sutures or double running sutures with less than 16 bites in minimizing astigmatism postoperatively while sutures are in place.…”
Section: Suturing Technique and Suture Materialsmentioning
confidence: 99%
“…31,32 Final astigmatism is almost the same with single running suture and double running suture techniques. 33 Other authors have shown that an adjustable single running suture is better than a double running suture in managing postsurgical astigmatism. 34 Busin et al 30 report that double running sutures with 16 bites each are superior to 16 interrupted sutures or double running sutures with less than 16 bites in minimizing astigmatism postoperatively while sutures are in place.…”
Section: Suturing Technique and Suture Materialsmentioning
confidence: 99%
“…However, although it has been used for some time and there is profuse literature on its short-and medium-term results [2,3,9,22,23,24], documentation of long-term results is sparse [25], and the data that have been published are all based on average perspectives of 3-10 years following surgery [4,8,13,16,19,20,21,26,27]. While penetrating keratoplasty appears very successful with an overall 1-year survival rate as high as 90% [27], the long-term reality is that the overall success rate progressively diminishes at 5 years and 10 years [27].…”
Section: Introductionmentioning
confidence: 98%
“…[3][4][5][6][12][13][14][15][16][17][18][19][20][21][22] Most relevant studies are retrospective, 3,6,12,13,17,19 compare 2 suturing techniques, and consist of a heterogeneous group of patients with diverse etiologies including, but not restricted to, keratoconus. [1][2][3][4][5][6][12][13][14][15][16][17][18][19][20][21][22] This randomized clinical trial evaluates the role of the 3 common suturing techniques on postkeratoplasty astigmatism exclusively in patients with keratoconus.…”
mentioning
confidence: 99%
“…5,6 Patients with keratoconus constitute an important group because of the high prevalence, younger age of onset, active lifestyle, and higher visual requirements. 7 Factors that may affect postkeratoplasty astigmatism include suturing technique, [3][4][5][6]8 type and size of trephines, [9][10][11] time of suture removal or adjustment, [12][13][14][15][16] apposition of donor and recipient tissues, 17 oval or eccentric trephination, 9 and donor-recipient disparity. 11 Different suturing techniques have been applied for PKP including interrupted (IR), single running (SR), double running (DR), and combined interrupted and running (CIR), each with its own benefits and drawbacks.…”
mentioning
confidence: 99%